Conference Record of the Twenty-Eighth IEEE Photovoltaic Specialists Conference - 2000 (Cat. No.00CH37036)
DOI: 10.1109/pvsc.2000.915991
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancement of amorphous silicon p-i-n solar cells by LP-CVD ZnO

Abstract: Amorphous silicon p-i-n solar cells were deposited on "in house" developed LP-CVD zinc oxide and compared with commercially available SnOa (Asahi type U2) substrates.While for both front TCO materials comparably high values of the open circuit voltage (860-900 mV) and of the fill factor (72 -74 %) were obtained, a remarkable enhancement of the short-circuit current density could be observed for LP-CVD ZnO substrates. Optical characterizations confirm for LP-CVD ZnO a more efficient light-trapping effect, as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 4 publications
3
23
0
Order By: Relevance
“…5) as compared to SnO 2 (type U) [17]. Our amorphous silicon p-i-n solar cells on LP-CVD ZnO TCO have independently been confirmed by NREL with an initial efficiency of 10.6% (1 cm 2 ) and a high open circuit voltage of 900 mV.…”
Section: Light-trappingsupporting
confidence: 62%
“…5) as compared to SnO 2 (type U) [17]. Our amorphous silicon p-i-n solar cells on LP-CVD ZnO TCO have independently been confirmed by NREL with an initial efficiency of 10.6% (1 cm 2 ) and a high open circuit voltage of 900 mV.…”
Section: Light-trappingsupporting
confidence: 62%
“…The approximately 400 nm thick ilayer was deposited at a silane gas phase concentration close to the a-Si:H/lc-Si:H transition. The underlying substrate material is a sodium-free AF-45 glass substrate coated with ZnO deposited by low pressure chemical vapor deposition, the latter being a rough transparent conductive oxide used for solar cells applications [8]. An AFM height scan (scan range of 1 lm, 512 · 512 measurement points) of the substrate (here solar-grade LPCVD ZnO) has been used as a discrete height map for the computer simulations.…”
Section: Growth Experiments and Measurementsmentioning
confidence: 99%
“…In order to fill this gap, we base our understanding on previous work showing that the morphology observed at the surface of LP-MOCVD ZnO results from a combination of both nucleation-and kinetic-driven phenomena [8][9][10][11][12][13][14][15][16][17]. In fact, it was demonstrated that temperature induced inter-facet diffusion could lead to the selection of different crystallographic PO [8].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, due to the relatively small values of the amorphous and microcrystalline silicon (a-Si:H and mc-Si:H) absorption coefficients, the optical path of the light inside the active layers of Si PV cells has to be increased to enhance the photo-generated current. One possible solution to achieve this goal is to use nano-textured TCO surfaces [9]. In contrast to LP-MOCVD layers, sputtered ZnO films require one additional wet etching process step to achieve a rough lightscattering surface [5].…”
Section: Introductionmentioning
confidence: 99%